A new species of Omphalocyclus Bronn, O. omanensis sp. nov., from the upper Campanian of Oman: Phylogenetic and stratigraphic implications - Kaygili, Sibel; Yucel, Ali O.; Abbasi, Iftikhar A.; Catanzariti, Rita; Ozcan, Ercan (Academic Press Ltd- Elsevier Science Ltd, 2021)
The genus Omphalocyclus Bronn is a Late Cretaceous orbitoidal larger foraminifera, usually considered as a marker for the Maastrichtian. Herein we describe Omphalocyclus specimens from the upper part of the Qahlah Formation in North Oman, probably representing the most primitive developmental stage of the genus in the Tethys. The studied specimens are characterized by having delicate discoidal, biconcave tests with a notably small, 'trilocular' embryonic apparatus and a few (usually 2) epi-embryonic chamberlets. The embryonic wall in some specimens is thin and hardly discernible as a separate morphological entity compared to following chamberlets. Duplication of the annular series of chamberlets in the equatorial plane (equatorial layer), a characteristic morphological feature of the genus, is observed at a late ontogenetic stage. After comparison of these specimens with specimens of type-species O. macroporus (Lamarck) from the Simsima Formation in Oman and previously described species (e.g., O. anatoliensis Ozcan, O. cideensis Ozcan, O. maldonensis Gunter, Robinson, Mitchell), a new species, O. omanensis sp. nov. is established. The stratigraphic distribution of the genus is updated, and a tentative phylogenetic scheme is proposed. The upper part of the Qahlah Formation in the Buraymi region is assigned to the upper Campanian based on the recognition of calcareous nannofossils Zones CC22b and CC23a and the occurrence of Orbitoides medius (d'Archiac). (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Larger foraminifera; Systematics; New species; Late Campanian; Qahlah Formation; Oman